Señorita Mariposa - G, Mister; Almada Rivero, Marcos (New York : Nancy Paulsen Books, 2019)
Illustrations and easy-to-read text in English and Spanish follow monarch butterflies on their journey from Canada to Mexico. Includes author's note on how to help protect monarch butterflies.
In English and Spanish.
Keywords: Stories in rhyme; Monarch butterfly -- Migration -- Juvenile fiction; Butterflies -- Juvenile fiction; Spanish language materials -- Bilingual; Cuentos en ritmo; Mariposa monarca -- Migracion -- Novela juvenil; Mariposas -- Novela juvenil; Picture books for children